Plan de mantenimiento predictivo en una línea de llenado para detergente concentrado líquido - Velástegui, A. (2011)
In this thesis we show how to make a “Predictive Maintenance Plan on Filling Line for Liquid Detergent Concentrate”, focus on give you a dependable guide about types and frequency of equipment maintenance. The control of this will be made by operators of the line and supervised by maintenance department. Equipment involved directly and indirectly with production line, was identify by observation; by this way we start to detail maintenance frequency suggested by technique manuals of each equipment, also supplementing by line operators suggestions, technical of maintenance department of the company and specializes companies. All this analysis concludes the elaboration of a daily, weekly and monthly plan of predictive maintenance of critical equipment. This plan includes three principal activities: inspection, cleaning and a general periodic maintenance. This activities will maintain a well functioning and extend the useful life of the equipments.